Toward Excellent Islamic Boarding Schools: Reconstructing Educational Governance Based on Pesantren Values - Abdul Halim; Kojin Kojin; Ahmad Tanzeh; Wardani Wardani; Rohiqi Mahtum (Institut Agama Islam Sunan Giri Ponorogo, 2026)
Islamic boarding schools (pesantren) are increasingly required to improve their educational quality and global competitiveness while preserving their distinctive Islamic identity and traditional values. This study addresses the need to reconstruct educational governance based on pesantren values as a sustainable strategy for institutional excellence. The purpose of this study is to develop a value-based educational governance model that integrates indigenous pesantren philosophy with contemporary governance principles. A qualitative multi-case study design was employed involving three Indonesian Islamic boarding schools. Data were collected through semi-structured interviews, participant observation, document analysis, and field notes, and analyzed using the interactive model of data condensation, data display, and conclusion drawing with cross-case synthesis. The findings reveal that effective educational governance is built upon the integration of core pesantren values—ikhlas, amanah, syura, ukhuwah, ta'awun, tawassuth, and istiqamah—with transformational leadership, integrated quality assurance, digital governance, collaborative partnerships, and international engagement. Based on these findings, the study proposes the Excellent Islamic Boarding School Governance Model (EIBSGM) as a comprehensive framework for strengthening institutional quality while maintaining religious authenticity. The study concludes that governance reconstruction should prioritize the transformation of pesantren values into strategic governance principles rather than replacing traditional governance systems, thereby enabling Islamic boarding schools to achieve sustainable excellence and global competitiveness